No Innate Phases in Group Problem Solving - Seeger, John A. (Academy of Management Review, 1983)
A widely accepted empirical study (Bales & Strodtbeck, 1951)) concludes that “many staff conferences, committees, and similar groups” progress through predictable sequential phases in problem solving. Reexamination suggests that the conclusion is wrong. Only those subject groups that had never before met showed phased movement. The 1951 research may have measured the process of group formation, not problem solving. Well-acquainted small groups—for example, most management teams, task forces, and committees—do not naturally follow sequential phases in problem solving.